The Psychometric Properties of the Norwegian version of Resilience Scale for Adolescents (READ) - Askeland, Kristin Gärtner; Reedtz, Charlotte (PsykTestBarn, 2015)
Description: Resilience Scale for Adolescents (READ) is a self-report questionnaire measuring resilience; the ability to handle stress and negative experiences. It was developed in 2006 by Hjelmedal, Friborg, Stiles, Martinussen and Rosenvinge. READ is a 28-item scale with positively formulated items organized in five subscales; personal competence, social competence, social support, family cohesion and structured style. It takes five minutes to complete the questionnaire. READ is copy protected and the copy right holders can be contacted to gain access to the test. Literature search: The literature search resulted in 55 original publications, 10 of which were included. Nine of the included studies are cross-sectional and have assessed READ in general populations of adolescents from 13 to 21 years old. Psychometrics: Eight of the included studies reported mean values in general populations, some separately for boys and girls. Two studies examined the factor structure of READ, four studies reported correlations with measures of mental difficulties, and three studies investigated the predictive properties of READ. Measures of internal consistency (Chronbach’s alpha) were included in seven of the studies. Conclusion: READ shows adequate psychometric properties and promising validity when correlated with measures of mental difficulties. The internal consistency is adequate for four of five subscales. READ is well suited for research purposes, however, there is no available documentation on applications in clinical settings.